Quantitative Structure–Activity Relationships for the Nucleophilicity of Trivalent Boron Compounds. Issue 21 (28th March 2017) - García‐López, Diego; Cid, Jessica; Marqués, Ruben; Fernández, Elena; Carbó, Jorge J.
Abstract: We describe herein the development of quantitative structure–activity relationships (QSAR) for the nucleophilicity of trivalent boron compounds covering boryl fragments bonded to alkali and alkaline‐earth metals, to transition metals, and to sp 3 boron units in diboron reagents. We used the charge of the boryl fragment ( q [B]) and the boron p/s population ratio ( p / s ) to describe the electronic structures of boryl moieties, whereas the distance‐weighted volume ( V w ) descriptor was used to evaluate the steric effects. The three‐term easy‐to‐interpret QSAR model showed statistical significance and predictive ability ( r 2 =0.88, q 2 =0.83). The use of chemically meaningful descriptors has allowed identification of the factors governing the boron nucleophilicity and indicates that the most efficient nucleophiles are those with enhanced the polarization of the B−X bond towards the boron atom and reduced steric bulk. A detailed analysis of the potential energy surfaces of different types of boron substituents has provided insight into the mechanism and established an order of nucleophilicity for boron in B−X: X=Li>Cu>B(sp 3 )>Pd. Finally, we used the QSAR model to make a priori predictions of experimentally untested compounds. Abstract : Predictive ability : A quantitative structure–activity relationship model for the nucleophilicity of trivalent boron compounds that shows statistical significance and predictive ability, allowing a priori predictions of experimentally untested compounds, was developed. The chemical space includes boryl fragments bonded to alkali and alkaline‐earth metals, to transition metals, and to sp 3 boron units in diboron reagents activated by Lewis bases (see figure).